An overview of take-home naloxone programs in Australia - Dwyer, Robyn; Olsen, A.; Fowlie, C.; Gough, C.; van Beek, I.; Jauncey, M.; Lintzeris, N.; Oh, G.; Dicka, J.; Fry, C.; Hayllar, J.; Lenton, Simon (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Australasian Professional Society on Alcohol and other Drugs. Introduction and Aims: Take-home naloxone (THN) programs commenced in Australia in 2012 in the Australian Capital Territory and programs now operate in five Australian jurisdictions. The purpose of this paper is to record the progress of THN programs in Australia, to provide a resource for others wanting to start THN projects, and provide a tool for policy makers and others considering expansion of THN programs in this country and elsewhere. Design and Methods: Key stakeholders with principal responsibility for identified THN programs operating in Australia provided descriptions of program development, implementation and characteristics. Short summaries of known THN programs from each jurisdiction are provided along with a table detailing program characteristics and outcomes. Results: Data collected across current Australian THN programs suggest that to date over 2500 Australians at risk of overdose have been trained and provided naloxone. Evaluation data from four programs recorded 146 overdose reversals involving naloxone that was given by THN participants. Discussion and Conclusions: Peer drug user groups currently play a central role in the development, delivery and scale-up of THN in Australia. Health professionals who work with people who use illicit opioids are increasingly taking part as alcohol and other drug-related health agencies have recognised the opportunity for THN provision through interactions with their clients. Australia has made rapid progress in removing regulatory barriers to naloxone since the initiation of the first THN program in 2012. However, logistical and economic barriers remain and further work is needed to expand access to this life-saving medication.